Coronectomy: two clinical case reports: Coronectomia: relato de dois casos clínicos - Rodrigues Martins, Bruna; Passos Magalhães, Leonor; Soares, Kaio Henrique; Lopes Martins, Olga Beatriz; Roberto Rocha dos Santos, Cássio (Revista Unimontes Científica, 2023)
Introduction: The lower third molar extraction is a procedure that can lead to some complications. To perform tooth extraction, the dental surgeon requests imaging exams to assess some aspects, including the proximity of the tooth to the inferior alveolar nerve. Based on these findings, the surgery can be performed or other tests could be requested, such as a cone beam computed tomography. If the proximity between such structures is confirmed through tomography, the coronectomy presents as an alternative to conventional third molars or other mandibular teeth extractions that are in close contact with the inferior alveolar nerve and, consequently, with a higher risk of damaging this structure. Objective: The present study aims to report two clinical cases of coronectomy performed at the oral surgical clinic of the Federal University of Jequitinhonha and Mucuri Valleys (UFVJM). Methodology: Two clinical cases were reported in this study. Discussion: Although the results of this technique are positive, it second surgical procedure to remove residual roots. Conclusion: In both cases, no complications were reported by the patients, such as loss of sensitivity, pain, infection or dry socket.